Immune-molecular nexus in reproductive disorders: mechanisms linking POI and RSA - Chen, Chen; Zhang, Xinyue; Li, Wenxin; Liu, Yueqin; Zhao, Dan; Zhang, Subo; Zhu, Xiaolan (Frontiers in Genetics, 2025)
BackgroundInfertility remains a prevalent global health concern, with Premature Ovarian Insufficiency (POI) and Recurrent Spontaneous Abortion (RSA) being common causes of female infertility.ObjectiveThis study aims to identify new central genes and potential therapeutic drugs for RSA and POI by integrating multi transcriptome data and machine learning algorithms.MethodsThis study utilized RNA sequencing data from patients with POI and RSA to identify key hub genes associated with these diseases. The analysis involved machine learning algorithms, mcode and Cytoscape, revealing important hub genes. The comprehensive evaluation includes functional annotation, protein-protein interaction (PPI) network, transcription factor (TF) gene regulatory network, microRNA (miRNA) gene regulatory network. Genome enrichment analysis (GSEA) and immune infiltration studies elucidated the potential mechanism between POI and RSA. Drug target enrichment analysis highlighted promising therapeutic agents against RSA and POI. Validation of granulosa cells and endometrial tissue samples using quantitative real-time polymerase chain reaction (qRT-PCR) highlighted the importance of the identified hub genes.ResultsThis study identified a total of six hub genes—— CENPW, ENTPD3, FOXM1, GNAQ, LYPLA1, and PLA2G4A. Immunoassay revealed an increase in activated NK cells. Furthermore, significant differences were observed in the proportions of other immune cell types, such as resting memory CD4 T cells, compared to the control group. Significantly, these six genes participate in diverse metabolic pathways linked to RSA and POI, particularly in oxidative phosphorylation, ribosome processes, and steroid biosynthesis pathways. Additionally, ten potential drugs (Rifabutin, Methaneseleninic Acid, Carbamazepine, Dasatinib,Troglitazone, Tamoxifen, Enterolactone, Anisomycin, Testosterone, 5-Fluorouracil) targeting key genes were identifed.ConclusionTargeting these genes shows promise for preventing and treating both POI and RSA, providing crucial insights into addressing these complex conditions at molecular level.